2020
DOI: 10.2147/orr.s243444
|View full text |Cite
|
Sign up to set email alerts
|

<p>Being Underweight Is Associated with Worse Surgical Outcomes of Total Knee Arthroplasty Compared to Normal Body Mass Index in Elderly Patients</p>

Abstract: Being underweight has never been studied in relation to the radiologic and clinical outcomes of total knee arthroplasty (TKA) in elderly patients. The aim of this study was to determine the effect of being underweight on TKA radiological and clinical outcomes and to investigate whether being underweight influences postoperative complications compared to normal body mass index (BMI) in elderly patients. Patients and Methods: A total of 118 female patients aged 65 years or older with BMI < 25 kg/m 2 who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…16-18 More recently, underweight BMI has been identified as a predictor for mortality, increased complications, and increased length of stay after primary TJA. 19-23 Similarly, these findings were duplicated in a recent total shoulder arthroplasty study by Ottesen et al, 24 which demonstrated an increased risk of adverse events in underweight patients. To the authors' knowledge, this study is the first to identify underweight BMI as a risk factor for increased complications and length of stay after rTJA.…”
Section: Discussionmentioning
confidence: 76%
“…16-18 More recently, underweight BMI has been identified as a predictor for mortality, increased complications, and increased length of stay after primary TJA. 19-23 Similarly, these findings were duplicated in a recent total shoulder arthroplasty study by Ottesen et al, 24 which demonstrated an increased risk of adverse events in underweight patients. To the authors' knowledge, this study is the first to identify underweight BMI as a risk factor for increased complications and length of stay after rTJA.…”
Section: Discussionmentioning
confidence: 76%
“…A total of eighteen studies[ 10 , 11 , 19 - 34 ] were included in this review. Twenty-two eligible studies[ 4 , 35 - 37 ] were screened from a pool of 671 records identified from both electronic and manual searches, purely based on title and abstract.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen retrospective cohort studies[ 10 , 11 , 19 - 23 , 25 , 26 , 28 , 29 , 31 , 33 ] and five prospective cohort studies[ 24 , 27 , 30 , 32 , 34 ] were included. The studies included a total of 1136506 subjects undergoing TKA or THA with a mean age of 65.32 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations